Factors Contribute to Employees Motivations towards Individual Output Performance in Telco Company - Siti Sakinah, Ab. Rahim (2009)
Many researches have been done on employee motivation.There are so many factors reveals can promotes to employee motivation. However, none of the experiential study has contended the relationship of employee motivation with an individual output performance. Thus, the purpose of this exploratory study was To identify the best factor promotes to employee motivation and to see the relationship between employee motivation and individual performance. The rationale for the study derives from the researcher’s desire to understand more on the association of employee motivation towards the output performance and use these insights to guide the development of employee affairs especially on motivation and performance. The research has been conducted using survey method which 250 number of respondents have answering the questionnaire. Data from the study were then been analyzed using SPSS (Statistical Package for Social Science) to produce the accurate findings. This research revealed factors that promotes more on employee motivation and the relationship between individual output performance with motivated employee. The research also suggests that organization or management team should aware of each individual behavior in order to seek the motivation factors as each individual hold difference character.